Emergency Contraception Access and Counseling in Urban Pharmacies: A Comparison between States with and without Pharmacist Prescribing - Rebecca H. Stone; Sally Rafie; Dennia Ernest; Brielle Scutt (MDPI AG, 2020)
Pharmacists are often the primary source of emergency contraception (EC) access and patient information. This study aims to identify differences in pharmacist-reported EC access and counseling between states which do or do not permit pharmacist-prescribed EC. This prospective, mystery caller study was completed in California (CA), which permits pharmacist-prescribed EC after completion of continuing education, and Georgia (GA), which does not. All community pharmacies that were open to the public in San Diego and San Francisco, CA, and Atlanta, GA were called by researchers who posed as adult females inquiring about EC via a structured script. Primary endpoints were EC availability and counseling. Statistical analyses completed with SPSS. Researchers called 395 pharmacies, 98.2% were reached and included. Regarding levonorgestrel (LNG), CA pharmacists more frequently discussed (CA 90.4% vs. GA 81.2%, p = 0.02), stocked (CA 89.5% vs. GA 67.8%, p < 0.01), and correctly indicated it "will work" or "will work but may be less effective" 4 days after intercourse (CA 67.5% vs. GA 17.5%, p < 0.01). Ulipristal was infrequently discussed (CA 22.6% vs. GA 3.4%, p < 0.01) and rarely stocked (CA 9.6% vs. GA 0.7%, p < 0.01). Pharmacists practicing in states which permit pharmacist-prescribed EC with completion of required continuing education may be associated with improved patient access to oral EC and more accurate patient counseling.